Biological activities of dengue virus on murine macrophages - Rajamani, Leela; Aziz, Nadia; Sekaran, Shamala Devi (Faculty of Medicine, University of Malaya, 1997)
The biological activities of dengue 2 virus on its target cells, namely macrophages and neutrophils were investigated. Preliminary results showed that polyethylene glycol precipitated dengue 2 virus acted as a chemoattractant for peritoneal cells of Balbc/I mice and for established rnonoctyesfmacrophage cell lines (WEHI 265.1). This in nine response was also seen in vitro using Boyden Chemotaxis chambers and was found to be inhibited by specific viral antibodies. The ability of the virus to activate these cells was then evaluated. Treatment of the peritoneal cells with virus induced a respiratory burst with the production of picomoles of superoxides. In addition, the virus induced production of reactive nitrogen intermediates (1-2 uM) and also resulted in exocytosis of Iysozyme. Adhesiveness was also observed and appeared to increase with higher concentrations of the virus. The above results demonstrate that increased adhesiveness and activation are induced following treatment of peritoneal cells and the cell line WEHI 265.1 with dengue virus.